Meningkatkan hasil belajar materi pecahan dengan model Discovery learning pada Siswa Kelas IV Sekolah Dasar - Ratmurtiningsih, Lestari Dwi (Universitas Sebelas Maret, 2020)
This research is a Classroom Action Research (CAR). The research was conducted in two cycles with each cycle consisting of planning, implementing actions, observing and reflecting. The research subjects were the fourth grade students of SD Negeri 2 Tirtomoyo totaling 22 students. Meanwhile, the data sources were taken from (1) observations, (2) places, events, and behaviors, and (3) documents related to the research problem. The techniques used to collect the above data include observation, as well as document review. Data collection analysis techniques, namely using comparative descriptive analysis followed by reflection. At least students achieve 80% completeness of the desired indicators. The procedures used are (1) planning, (2) implementation, (3) observation, and (4) analysis and reflection. The results showed that the process of implementing learning with theModel Discovery Learning to improve learning outcomes of Class IV Fraction Materials at SDN 2 Tirtomoyo Tirtomoyo District, Baturetno Regency for the 2020/2021 Academic Year in accordance with the RPP that had been prepared, was more effective and increased from the poor category to good.